Предмет: Математика,
автор: Shbdfj
4-6•(х+2)=3-5х Помогите
Ответы
Автор ответа:
2
4 - 6 • (х + 2) = 3 - 5х
4 - 6х - 12 = 3 - 5х
6х - 5х = 4 - 12 - 3
х = -11
4 - 6х - 12 = 3 - 5х
6х - 5х = 4 - 12 - 3
х = -11
Автор ответа:
2
Ответ:4-6(x+2)=3-5x,
4-6x-12=3-5x,
-6x+5x=3-4+12,
-x=11,/x(-1)
X=11
Пошаговое объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: Аly
Предмет: Русский язык,
автор: КАРКАРЫЧ20094
Предмет: Другие предметы,
автор: Лола5557
Предмет: Алгебра,
автор: Ulitka2001
Предмет: Литература,
автор: klaiv47